Jasmonate-Responsive Transcription Factors NnWRKY70a and NnWRKY70b Positively Regulate Benzylisoquinoline Alkaloid Biosynthesis in Lotus (Nelumbo nucifera) - Li, Jing; Li, Yi; Dang, Mingjing; Li, Shang; Chen, Simeng; Liu, Ruizhen; Zhang, Zeyu; Li, Guoqian; Zhang, Minghua; Yang, Dong; Yang, Mei; Liu, Yanling; et al. (Frontiers in Plant Science, 2022)
Lotus (Nelumbo nucifera) is a large aquatic plant that accumulates pharmacologically significant benzylisoquinoline alkaloids (BIAs). However, little is known about their biosynthesis and regulation. Here, we show that two group III WRKY transcription factors (TFs), NnWRKY70a and NnWRKY70b, positively regulate BIA biosynthesis in lotus. Both NnWRKY70s are jasmonic acid (JA) responsive, with their expression profiles highly correlated to BIA concentration and BIA pathway gene expression. Dual luciferase assay showed that NnWRKY70a could transactivate NnTYDC promoter, whereas NnWRKY70b could activate promoters of three BIA structural genes including NnTYDC, NnCYP80G, and Nn7OMT. In addition, transient overexpression of NnWRKY70a and NnWRKY70b in lotus petals significantly elevated BIA alkaloid concentrations. Notably, NnWRKY70b seems to be a stronger BIA biosynthesis regulator, because it induced more dramatically BIA structural gene expression and BIA accumulation than NnWRKY70a. Yeast two-hybrid assay further revealed that NnWRKY70b physically interacted with NnJAZ1 and two other group III WRKY TFs (NnWRKY53b, and NnWRKY70a), suggesting that it may cooperate with other group III WRKYs to adjust lotus BIA biosynthesis via the JA signaling pathway. To illustrate the mechanism underlying NnWRKY70b-mediated BIA regulation in lotus, a simplified model is proposed. Our study provides useful insights into the regulatory roles of WRKY TFs in the biosynthesis of secondary metabolites.